Perancangan Sistem Pengukuran Kerja dengan Metode Intergrated Performance Measurement System (IPMS) (Studi Kasus: CV. Ekasari) - Indah Kurniyati; Risya Zeline; Sri Yohana Simanjuntak; Yuniaristanto - (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2016)
Global business competition greatly increased sharply in Indonesia, including in the food market. To succeed and grow in the competition, an organization should use measurement and management systems derived from the strategies and capabilities of the company. CV. Eka Sari is a company engaged in the field of catering, where business activity in CV. Eka Sari is more focused on providing the bread and cakes. The continued development of the catering business, demanding CV. Eka Sari to improve in every aspects of company performance, so that the company can remain competitive with other companies. Therefore, CV. Eka Sari is in need of performance measurement that aims to evaluate and plan its performance in order to achieve organizational goals. Performance measurement methods used by the company is Integrated Performance Measurement System (IPMS), which is a method that measures the performance of an integrated and based on the wishes of stakeholders. Objectives are determined to meet the wishes of stakeholders, so that will be determined key performance indicators. From the results of the identification, obtained 22 key performance indicators. To determine the performance criteria that need more attention then be weighted. Weighting is done using Hierachy Analytical Process (AHP). Weighting results generated from that aspect that must be considered are aspects of the process, then the performance criteria that must be considered, namely improving the efficiency and effectiveness of production, and Key Performance Indicators to be very aware of is the number of defective products.